Association of antibodies to the NR1 subunit of N-methyl-D-aspartate receptors with neuropsychiatric systemic lupus erythematosus. Issue 3 (3rd May 2016) - Ogawa, Eisuke; Nagai, Tatsuo; Sakuma, Yuko; Arinuma, Yoshiyuki; Hirohata, Shunsei
Abstract: Objective : To determine epitope reactivity of autoantibodies to N -methyl-D-aspartate (NMDA) receptor NR1 subunit and their association with neuropsychiatric systemic lupus erythematosus (NPSLE). Methods : Paired serum and CSF specimens were obtained from 41 patients with NPSLE (22 with diffuse psychiatric/neuropsychological syndromes [diffuse NPSLE] and 19 with neurologic syndromes or polyneuropathy [focal NPSLE]), 21 patients with various rheumatic diseases other than SLE (non-SLERD). Sera were also obtained from 27 SLE patients without neuropsychiatric manifestations (non-CNS SLE). Antibodies to murine NR1 (mNR1) or to 4 different preparations of synthetic 25-amino-acid (AA) peptides of human NR1 were measured by enzyme-linked immune sorbent assay (ELISA). Results : Serum anti-mNR1 levels were significantly higher in NPSLE than in non-SLERD. Sera from NPSLE patients bound efficiently to the AA residues 19–44 from the N -terminus of NR1 (NR1-A) or 56–81 (NR1-C). Accordingly, serum anti-NR1-A and anti-NR1-C were also elevated in NPSLE compared with non-SLERD. Of note, anti-NR1-A as well as anti-NR1-C levels in CSF, but not in sera, were significantly elevated in diffuse NPSLE compared with focal NPSLE or with non-SLERD. Conclusion : These results suggest that autoantibodies to NMDA receptor NR1, especially to the AA residues 19–44 and 56–81 from the N -terminus play a pivotal role in the pathogenesis of diffuse NPSLE.